Vulvar sarcomas: clinical and morphological observations and a review of literature - E. V. Korzhevskaya; V. V. Kuznetsov (Опухоли женской репродуктивной системы, 2014)
Vulvar sarcomas are extremely rare tumors. They account for less than 1